Kajian terhadap penggunaan IBS dalam projek swasta di kawasan Lembah Klang - Mohd Nawi, Mohd Nasrun; Azman, Mohamed Nor Azhari; Mohamad Kamar, Kamarul Anuar; Abd Hamid, Zuhairi (Penerbit UTM Press, 2013)
The construction sector based on industry or lndustrialised Building System is a method of construction using the industrialised building materials at the manufacturing plant.This method can replace the conventional method which is able to reduces the amount of foreign labor as well as to improve the quality of construction, lower cost and reduction in construction time.This study is intended to create a guideline that can be used to encourage all private construction projects In the Klang Valley implement the IBS System in 2015.Therefore, this study was undertaken to assess the level of IBS usage in the building construction. There are about 400 private sector projects in the Klang Valley has been identified as a sample for this study in which 184 private projects are using IBS technology achieved a score of 55% and above.The findings of this study had identify the perceptions, barriers exist and the measures to be taken in the implementation and the criteria for developing a business model that can be used to be a concept of IBS in the private sector.